It's Time to Take Action: Acoustic Modeling of Motor Verbs to Detect Parkinson's Disease - Escobar-Grisales, Daniel; Ríos-Urrego, Cristian David; Baumann, Ilja; Riedhammer, Korbinian; Nöth, Elmar; Bocklet, Tobias; Garcia, Adolfo M.; Orozco-Arroyave, Juan Rafael (Proceedings of the Annual Conference of the International Speech Communication Association, INTERSPEECH, 2024)
Pre-trained models generate speech representations that are used in different tasks, including the automatic detection of Parkinson's disease (PD). Although these models can yield high accuracy, their interpretation is still challenging. This paper used a pre-trained Wav2vec 2.0 model to represent speech frames of 25ms length and perform a frame-by-frame discrimination between PD patients and healthy control (HC) subjects. This fine granularity prediction enabled us to identify specific linguistic segments with high discrimination capability. Speech representations of all produced verbs were compared w.r.t. nouns and the first ones yielded higher accuracies. To gain a deeper understanding of this pattern, representations of motor and non-motor verbs were compared and the first ones yielded better results, with accuracies of around 83% in an independent test set. These findings support well-established neurocognitive models about action-related language highlighted as key drivers of PD.
CRIS-Team Scopus Importer:2025-02-04
Keywords: action verbs; computational paralinguistics; interpretability of pre-trained models; Parkinson's disease